2010
DOI: 10.5301/jva.2010.5831
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition, Infection and Arteriovenous Fistula Failure: Is There a Link?

Abstract: Our study suggests that CMV infection, total plasma cholesterol, decreased Qac, and nPCR are important risk factors of AVF failure in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
47
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 21 publications
2
47
0
Order By: Relevance
“…Several studies have shown that VAF is linked to many variables, including age, sex, diabetes, total cholesterol, cardiovascular disease, and vascular access type, along with many others [2830]. This study showed that an increase in MPV/platelet count ratio over time was independently associated with VAF.…”
Section: Discussionsupporting
confidence: 52%
“…Several studies have shown that VAF is linked to many variables, including age, sex, diabetes, total cholesterol, cardiovascular disease, and vascular access type, along with many others [2830]. This study showed that an increase in MPV/platelet count ratio over time was independently associated with VAF.…”
Section: Discussionsupporting
confidence: 52%
“…Patients with diabetes mellitus have elevated serum coagulation factors and impaired fibrinolysis due to elevated concentrations of plasminogen activator inhibitor-1 (PAI-1), resulting in a higher frequency of atherothrombotic events as well as venous thrombosis [6][8]. High anti-Cytomegalovirus IgG levels have also been identified as an independent risk factor for AVF thrombosis [9], [10] but we were unable to confirm these findings [11].…”
Section: Introductionmentioning
confidence: 82%
“…However, the detailed pathogenesis and relevant mediators of VA stenosis remain under investigation. Gagliardi et al [32] showed that neointimal hyperplasia is histopathologically similar to atherosclerosis. Furthermore, uremic atherosclerosis is associated with inflammation [23] , which in turn was shown to play a critical role in the development of VA stenosis [33][34][35] .…”
Section: Discussionmentioning
confidence: 99%